The intimate supply chain leveraging the supply chain to manage the customer experience - Ross, David Frederick 1948- (Auerbach Publications, 2008)
Presents a paradigm shift in supply chain thinking. This book explains how effective supply chain management must start with the aim of being as intimate with the customer as possible in order to bring total value to the customer's experience.
Includes bibliographical references and index. - Print version record
Keywords: Business logistics; Customer relations; Logistique (Organisation)